GROUP CLASSIFICATION OF LINEAR SECOND-ORDER DELAY ORDINARY DIFFERENTIAL EQUATION - Prapart Pue-on (Proceedings of ICMSA, 2006)
The linear delay ordinary differential equationy”(x) + a(x) y’(x) + b(x) y’(x −τ ) + c(x) y(x) + d(x) y(x −τ ) = g(x)is studied, where the coefficients a(x),b(x), c(x) and d(x) and function g(x) are arbitrary. In this manuscript, group analysis is applied to find equivalent symmetries of the equation.